Business and Competitive Analysis: Effective Application of New and Classic Methods (paperback) - Fleisher, Craig S. (Journal of Sustainable Competitive Intelligence, 2012)
I believe that this book will fill a great need for both full-time competitive intelligence practitioners, and those looking to add analytical skills to their managerial tool kit.” –Bill Fiora, Partner and Founder, Outward Insights “All practicing managers and business decision makers should be grateful to Fleisher and Bensoussan for showing them how their analysis work can become more rigorous and their approach less casual. Accept no imitations. This is the genuine article.” –Sheila Wright, Director of the Competitive Intelligence-Marketing Interface Teaching and Research Initiative (CIMITRI) at Leicester Business School, De Montfort University The Definitive How-To Guide for Business and Competitive Analysis Transform raw data into compelling, actionable business recommendations Answer the questions executives ask–“What?” “So What?” and “Now What?” Today’s 24 most valuable techniques: how to choose them, how to use them For everyone who performs analysis: managers, consultants, functional specialists, and strategists A completely new book by the authors of the popular Strategic and Competitive Analysis Business success begins with deep clarity about your competition and your business environment. But, even as data gathering has improved dramatically, few business professionals know the state-of-the-art techniques for analyzing their data. Now there’s a comprehensive, immensely practical guide to today’s best tools and techniques for answering tough questions and making actionable recommendations. Business and Competitive Analysis begins with end-to-end guidance on the analysis process, including defining problems, avoiding analytical pitfalls, choosing tools, and communicating results. Next, the authors offer detailed guides on 24 of today’s most valuable analysis models: techniques that have never been brought together in one book before.They offer in-depth, step-by-step guidance for using every technique–along with realistic assessments of strengths, weaknesses, feasibility, and business value. You are flooded with data. This book will help you transform that data into actionable insights and recommendations that enterprise decision makers cannot and will not ignore. Craig S. Fleisher and Babette E. Bensoussan begin with a practical primer on the process and context of business and competitive analysis: how it works, how to avoid pitfalls, and how to communicate results. Next, they introduce their unique FAROUT method for choosing the right tools for each assignment. The authors then present 24 of today’s most valuable analysis methods.They cover “classic” techniques, such as McKinsey 7S and industry analysis, as well as emerging techniques from multiple disciplines:economics,corporate finance, sociology, anthropology, and the intelligence and futurist communities. For each, they present clear descriptions, background context, strategic rationales, strengths, weaknesses, step-by-step instructions, and references. The result is a book you can rely on to meet any analysis challenge, no matter how complex or novel. The fundamentals of business and competitive analysis Goals, processes, pitfalls, deliverables, and benefits Competitive analysis techniques Nine Forces, Competitive Positioning, Business Model, SERVO, and Supply Chain Analyses Enterprise analysis techniques Benchmarking, McKinsey 7S, Shadowing, Product Line, and Win/Loss Analyses Environmental analysis techniques Strategic Relationships, Corporate Reputation, Critical Success Factors, Driving Forces, and Country Risk Analyses Evolutionary analysis techniques Technology Forecasting,War Gaming, Event/Timeline, Indications and Warning Analyses, and more Financial, probabilistic, and statistical techniques Basic Statistics, Competitor Cash Flow, Analysis of Competing Hypothesis (ACH), and Linchpin Analyses Table of Contents: Preface 1. Business and Competitive Analysis: Definition, Context, and Benefits 2. Performing the Analysis Process 3. Avoiding Analysis Pitfalls 4. Communicating Analysis Results 5. Applying the FAROUT method 6. Industry Analysis (The Nine Forces) 7. Competitive Positioning Analysis 8. Business Model Analysis 9. SERVO Analysis 10. Supply Chain Management (SCM) Analysis 11. Benchmarking Analysis 12. McKinsey 7S Analysis 13. Shadowing 14. Product Line Analysis 15. Win/Loss Analysis 16. Strategic Relationship Analysis 17. Corporate Reputation Analysis 18. Critical Success Factors Analysis 19. Country Risk Analysis 20. Driving Forces Analysis 21. Event and Timeline Analysis 22. Technology Forecasting 23. War Gaming 24. Indications and Warning Analysis 25. Historiographical Analysis 26. Interpretation of Statistical Analysis 27. Competitor Cash Flow Analysis 28. Analysis of Competing Hypothesis 29. Linchpin Analysis Book Description Publication Date: March 9, 2007 | ISBN-10: 0132161583 | ISBN-13: 978-0132161589 | Edition: 1 Clique Aqui